Aistear vis-à-vis the Primary Curriculum: the experiences of early years teachers in Ireland. Issue 2 (2nd April 2016) - Gray, Colette; Ryan, Anna
ABSTRACT: Launched in 2009, the Aistear early years curriculum framework sought to complement and extend the primary school curriculum (PSC) at infant class level in the Republic of Ireland. While Aistear focuses on the development of attitudes, values and learning dispositions and is neither statutory nor inspected, the PSC centres on the acquisition of subject-based knowledge and the development of age-appropriate skills, and is subject to external inspection. To explore teachers' experiences regarding the status of Aistear vis-à-vis the Curriculum, this study adopted a multi-method approach involving questionnaire surveys ( n = 104), one-to-one interviews ( n = 6) and classroom observations ( n = 6) to identify everyday practices in the classroom. Acknowledging the importance of play, there was little evidence that Aistear has transformed classroom teaching. Didactic teaching approaches remain dominant, with play afforded peripheral status. The study provides an original insight into the challenges teachers experience in meeting competing curricular demands.